ANALISIS DAMPAK APLIKASI TEKNOLOGI SIKLUS BARANG DAERAH DALAM MENINGKATKAN PENGAWASAN DAN AKUNTABILITAS PENGELOLAAN BARANG MILIK DAERAH (STUDI KASUS KECAMATAN SELAAWI) - Muhammad Haikal Hayatul Fazri; Lina Yulianti (PT. Hasba Edukasi Mandiri, 2025)
This study aims to analyze the application of technology applications in the management cycle of Regional Assets (BMD) and its impact on improving supervision and accountability in Selaawi District, Garut Regency. The study uses a qualitative method with a descriptive approach to describe the phenomenon of system implementation in a factual and in-depth manner. The results show that the use of the ATISISBADA application can improve the effectiveness of supervision through real-time asset data recording, integration between management cycles, and the provision of an audit trail that strengthens the internal control system. Reporting transparency also increases because asset data is centralized and automatically compiled in accordance with applicable accounting standards and regulations. However, the effectiveness of the application is still influenced by limited human resource competency and technical system constraints. Therefore, policies are needed to strengthen human resource capacity and continuous system updates so that this technology application can support the realization of accountable, efficient, and transparent regional asset management according to the principles of Good Governance.